Knöcherne und ligamentäre Verletzungen am ersten Strahl der Hand: CME : zertifizierte Fortbildung - Dinh-Biet, D. T. D; Leschinger, Tim; Müller, Lars Peter; Cavalcanti Kußmaul, Adrian; Unglaub, Frank; Spies, Christian (Die Unfallchirurgie, 2025)
Fractures and ligamentous lesions of the thumb ray are frequent due to the exposed position of the thumb. A thorough anatomical understanding with respect to the joints and stabilizing ligaments is essential for a targeted examination, the selection of appropriate imaging diagnostics and the decision for a surgical or conservative treatment approach. Misdiagnoses or untreated injuries can lead to impaired functionality, pain and instability, which can substantially impair the function of the hand, particularly thumb opposition.